2020
DOI: 10.1590/2177-9465-ean-2019-0079
|View full text |Cite
|
Sign up to set email alerts
|

Perception of elderly related to the risk of falls and their associated factors

Abstract: Objective: To analyze the association of the perception of the elderly on the risk factors for falls. Methods: An Analytical cross-sectional study with 190 elderly from the Healthy Longevity Program of a public university in Mato Grosso, from May to August 2016. The collection wasdone through a structured interview and vignettes. Performed descriptive and bivariate analyzes - Pearson chi-square test (x2) significance level of 5%. The crude and adjusted prevalence ratios (PR), with confidence intervals (95%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Among the guidelines offered, the main one was regarding the carpet removal and installation of non-slip floors. This study emphasizes the knowledge of seniors about falls and recommends that health professionals, particularly nurses, evaluate their risk perception regarding risk factors in daily life and advise on prevention measures ( 36 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Among the guidelines offered, the main one was regarding the carpet removal and installation of non-slip floors. This study emphasizes the knowledge of seniors about falls and recommends that health professionals, particularly nurses, evaluate their risk perception regarding risk factors in daily life and advise on prevention measures ( 36 ) .…”
Section: Discussionmentioning
confidence: 99%
“…However, a balance between precaution and restriction is necessary so that older adults do not limit their activities without real danger of falling and become insufficiently active. Thus, the greater the knowledge of the risks and factors involved in episodes of falls, the greater the individual's ability to make appropriate decisions regarding their behavior and, consequently, prevent these episodes [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the information mentioned above, it is suggested that socioeconomic and awareness aspects have an important role in the episodes of falls, since individuals with higher socioeconomic status have greater access to information and ease of learning, which may be able to increase their awareness related to risk factors for falls. Lack of knowledge leads individuals to greater exposure to risk situations 26 , so education and economic classification can be considered social determinants that can influence the search for health and modification of life habits 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The first meeting (T1) aimed to discuss the perception of susceptibility to falls of the elderly. Two activities were carried out: one, called "puzzle dynamics" and the other, "fall susceptibility" (34) , in which the elderly were distributed into small groups and given several printed vignettes in the form of a puzzle (35) with images of elderly people in situations of risk of falling. Then, the groups were asked to assemble the puzzles and discuss the questions: "(a) In this image, is there any situation of risk for the elderly to fall?…”
Section: Study Protocolmentioning
confidence: 99%